(untitled) (Kinesiology, 2017)
This study identified the short- and long-term effects of using a shooting strap on the accuracy of freethrows performed by U15 female basketball players during training and competition. Thirty six female basketball player volunteers (aged 14.3±0.5 years) from the Lithuanian Schoolchildren Basketball League were randomly assigned to either an experimental or control group. The experimental group used a shooting strap that immobilized movements of the supporting hand while shooting. The control group performed freethrows without any training aid. Learning and transfer of performance was assessed before and after the intervention training sessions (4-week intervention program applied 4 times per week), and on a retention test after one year. Results showed that: (a) free-throw accuracy was higher after one month and after one year of intervention than before the intervention training program in both practice and competition; (b) the experimental group scored better in practice and competition than the control group after one month and one year of the intervention; and (c) free-throw accuracy was higher during training sessions than during competition. The identified short-term and long-term improvements in free-throw shooting accuracy support the usage of shooting straps. The use of shooting straps and external assisting devices might allow adjusting programs of training to provide fluent free-throw accuracy progresses from youth to senior categories. Key words: technique, shooting training, team sports